PENGUATAN PENGGUNAAN BAHASA INDONESIA DI LINGKUNGAN MULTIBAHASA PADA SISWA SD NEGERI 4 SONI - Firnandha; Adinda Dwiutari; Desitriani; Yolpi Wukungsenggo (Makapande Mengabdi: Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2025)
This community service activity aims to strengthen the use of Indonesian in a multilingual environment, especially among students of SD Negeri 4 Soni, South Dampal District. The background of this activity is the low Indonesian language skills due to the dominance of regional languages ​​​​in everyday communication. Strengthening is carried out through the Real Work Lecture (KKN) program of students at Madako University Tolitoli with an interactive approach, communication habits, and the creation of simple learning media. The implementation method includes five strategic stages, namely initial observation, socialization and motivation, interactive learning, creation of learning media, and evaluation and reflection. The results of this activity show an increase in students' reading and writing skills, as well as the growth of positive attitudes towards improving Indonesian. The evaluation shows that reading skills increased from 60% to 80% and writing skills increased from 70% to 85%. In addition, the use of Indonesian language increased significantly in teaching and learning activities. This activity proves that a participatory and contextual approach can form a language ecosystem that supports the strengthening of national identity through language. This program also contributes to shaping students' character, as well as preserving the function of Indonesian amidst the diversity of regional languages.